Deaths in Turkish military services, 1998-2000 - (:unkn) unknown (ASSN MILITARY SURG US, 2004)
The aim of this study was to evaluate the causes of death in the military in Turkey and to evaluate the previously obtained data relating to the characteristics peculiar to the army in those cases of death that have acquired a juridical attribute. In this study, the cases presented in the years 1998 and 2000 have been investigated retrospectively. Seventy military cases investigated within a period of 3 years were all men. Except for the 20 cases in which the cause of death could not be determined, 30 of 50 cases in our study are included in the group of natural deaths and 20 are included in the group of forced deaths. In conclusion, natural causes are still the leading cause of death in Turkey, and regarding this, it can be suggested that these deaths could be preventable by better health care and more careful premilitary health examinations.